Connecting Domains in Concept-Context Learning: A model to analyse education situations - Koski, Marja-Ilona; Klapwijk, Remke; Vries, Marc de (Design and Technology Education: An International Journal, 2011)
The use of context-concept education alongside existing approaches is valuable. In this article we introduce a three-domain model for concept-context learning that supports both the design process as well as the idea of concept learning. The model shows how practical and abstract knowledge should be combined to improve contextconcept learning. The model acknowledges the dual nature of products and the need to relate practical, concrete experiences to causal explanations. It distinguishes three domains: the social context, the concrete product and the abstract knowledge domain. Here, the model is used to analyze, explain and suggest improvements for training primary school teachers in the Netherlands. The research data from the in-service teacher training show how continuous movement between the three domains is needed to develop creative, socially relevant solutions. The training would be better aimed towards the needs of the learner if the connection between the theory, concrete experiences with products and the social context is made more visible and inviting.